Method to integrate management tools aiming organizational excellence - Samuel Moretti Bernardo; Izabela Simon Rampasso; Osvaldo L.G. Quelhas; Walter Leal Filho; Rosley Anholon (Production)
Abstract Paper aims The main objective of this article is to present and validate a method to integrate multiple management tools aiming for organizational excellence in medium and large enterprises. Originality There is a scarcity of methods to integrate management tools to support companies in their operations. This study aims to fill this gap, proposing a manner for companies to perform this integration. Research method The method was developed considering tools and concepts well-established in the literature, such as Lean Thinking, Six Sigma, Balanced ScoreCard, among other management tools. The mentioned method was validated through a survey with managers and directors who are experts in organizational strategies. They were carefully selected considering their professional background. Main findings The proposed method provides an alignment between strategy and execution, presenting a cyclical characteristic to be continuously reviewed method, considering market needs. The survey verified the adherence of the method and to conclude that it is a feasible alternative to reach organizational excellence. Although integration of management methods is fundamental for companies to reach organizational excellence status, this kind of guidelines is scarce in the literature. Implications for theory and practice This method can be used to increase companies’ performance and competitivity.